Clinical and Laboratory Features of Intrauterine Infection - Omonova Guzal Zarifovna (Journal of Science in Medicine and Life, 2024)
Intrauterine infections are a group of diseases that develop as a result of infection of the fetus and newborn in the prenatal period or during childbirth. Intrauterine infections can cause fetal death, spontaneous abortion, intrauterine growth retardation, premature birth, birth defects, and damage to internal organs and the central nervous system. Diagnostic methods of intrauterine infections include microscopic, cultural, immunoenzyme and molecular biological studies. Treatment of intrauterine infections is carried out with the help of immunoglobulins, immunomodulators, antiviral and antibacterial drugs.